Using the Behavioural Factors to explain Perceived Project Performance of Ugandan Citizenship Projects: A Multivariate Analysis - Ahimbisibwe, Arthur; Nangoli, Sudi (International Journal of Business and Social Science, 2012)
The purpose of this paper was to develop and validate a causal modal of behavioural factors that explains perceived project performance of Ugandan Citizenship projects. Although numerous classical studies are reported in various contexts involving project communication, individual commitment, social networks and perceived project performance, no existing study focuses on how these four domains are linked together. Based on literature review, a theoretical model and 15 hypotheses were developed. A cross sectional data from a survey of 322 project staff of all 121 citizenship projects conducted by all 16 commercial banks in Uganda was used to validate the model. The results of Structural Equation Modelling support 11 of the 15 hypotheses and reveal that project communication does not influence perceived project performance directly but it influences it through the mediation of social networks and continuance commitment. Surprisingly, the study data did not support path coefficients between the other two individual commitment elements (affectivity and normative) and perceived project performance. Although these constructs are robust and sufficiently represent the behavioural aspects, the multidimensional nature of behavioural practises in perceived project performance can be investigated further. The individual commitment elements were expected to positively influence perceived project performance but did not. The use of case studies and additional surveys in future research might help to explain this surprising paradox. Further, since the future of project management practises go through evolution, additional ‘soft’ factors may be incorporated into the four domain causal model. The study results suggest that the social network elements fully mediate the relationship between project communication and perceived project performance. This implies that the corporate managers of citizenship projects need to develop strategies to create social networks with their stakeholders in order to increase perceived project performance.
Keywords: Project communication; Individual commitment; Social networks and Perceived project performance